Economic context of the Mexican crisis - Bannister, Geoffrey J. (Latin American Institute. University of New Mexico AlbuquerqueUS, 1996)
Presents a historical overview of economic reform in Mexico leading up to the financial crisis of 1994, begining with trade policy and complementaty policies for the liberalization of the domestic market. Reviews prinicipal outlines of macroeconomic reform and stabilization, leading to a brief account of the recent financial crisis and recent macroeconomic adjustment. Looks at recent developments in the structure of trade, bilateral trade relations and foreign direct investment. Concludes with some observations about Mexico's recovery from the 1994 crisis.